From the habitus to the unity of strength in Steinian thought: an opening for understanding the virtue in mourning - Mahfoud, Miguel; Queiroz, Maria Inês Castanha de (Argumentos - Revista de Filosofia, 2017)
The recurrence of the content of virtues in the narratives of mourners raised questions: Why and how the virtues emerge in mourning elaborations? This sparking question motivated the theoretical research by Husserl’s phenomenology that led us to the philosophical anthropology of Edith Stein. In the phenomenological description of the constitution of the human person, Stein introduced the concept of unity of force, a notion that she added to Thomistic thought and that allowed us to understand: the relationship between habitus, acts of will and virtue; the opening that the conception of habitus provides to understand the unity of the force in steinian thought; the dimension of the spirit as a source of force; the relationship between the dynamic of force with acts of will; the conception of virtue as actualization of potentiality in the spirit’s dimension. We conclude that virtue has specific connotation of habitus in its constitutive character of the person and has necessity of human action in the biopsychosocial and spiritual context to update and may prove to be a strengthening of personal expression.